BANK TRANSFERS IN THE ISLAMIC CIVILIZATIONASTIGMATISM AS A MODEL - Jinan Ahmed Abdulaziz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study dealt with a vital aspect of the economic history of the Arab Islamic civilization, as it shed light on one of the most important practices in bank transfers, which the Arab Islamic civilization had a great merit in its innovation and development, so that it contributed to saving effort and time and preserved money from loss and theft, in an easy way. And safe; Which contributed to the development of bank transfers and their prosperity among all the countries of the ancient world, and perhaps the West took this practice from them and guaranteed various commercial laws and regulations and adopted it in all their commercial practices to this day. This famous practice is known as Astigmatism, which naturally developed according to the development of global commercial systems and laws. It was surrounded by various laws that make it safer, more reliable and easier among merchants, and since there was no academic study concerned with collecting her diaspora and standing up for what she is and showing her merit over the economic life of the peoples of the ancient and modern world. A model), and we divided it into three topics, preceded by an introduction and followed by a conclusion. In the first topic we dealt with the definition of the vocabulary of the study, and in the second the dimensions and historical roots of the sophism and its development in Islamic civilization, and we devoted the third topic to its role in developing modern and contemporary commercial transactions.